The Influence of Learning Concentration That Reflects Disciplined Character on Mathematics Learning Outcomes at SMAN 1 Gondang - Anindita, Giezka Khaleda; Nurfadilah, Intan Siti (Sunan Kalijaga International Journal on Islamic Educational Research, 2025)
This study investigates the influence of learning concentration, as an indicator of disciplined character, on mathematics learning outcomes among Grade X students at SMA Negeri 1 Gondang. Employing a quantitative research design, data were collected from 108 students using validated and reliable self-report questionnaires measuring learning concentration and mathematics learning achievement. Descriptive statistics, assumption testing, and simple linear regression analysis were conducted using statistical software to examine the magnitude and significance of the relationship between variables. The results showed that the level of concentration and learning outcomes were in the high category, with a very strong relationship between the two variables (R = 0.885) and a contribution of 78.2% (R² = 0.782). The F test and the t-test showed a significant influence (p < 0.05), with the regression equation Ŷ = 33.627 + 0.822X. Overall, this study confirms that increasing learning concentration is one of the factors that increase student learning outcomes in mathematics lessons. The study highlights important implications for mathematics education practice, particularly the need for instructional strategies and classroom environments that intentionally foster concentration and self-regulation. However, the research is limited to a single school context and relies on a simple regression model, which may not capture the influence of other relevant factors. Future studies are recommended to involve more diverse samples, longitudinal approaches, and multivariate analyses to further explore the complex determinants of mathematics learning outcomes.